Gry językowe i zabawy słowne w zajawkach Faktów TVN-u - Dupel, Magdalena (Słowo. Studia językoznawcze, 2010)
Contemporary media determine the way of reception of reality, what is reflected in news services of various television stations. The aim of this article was the analysis of language and word games which appeared in zajawki in Fakty TVN at the turn of 2006 and 2007. Reporters who prepare daily news service with the use of appropriately selected words announce the most important news of the day in an interesting way and try to encourage a potential viewer to watch a certain program.